Physicochemical, antibacterial and antioxidant evaluation of cereal-based ethnic fermented Handia: An exploration for its food quality and health benefits from Mayurbhanj district in Odisha - Debasis Nayak; Susmita Rana; Tridev Shekhar Singha; Muskan Rai; Jibanjyoti Panda; Yugal Kishore Mohanta (Food and Humanity, 2026)

Therapeutic implications of targeting lipid metabolism and mitochondrial function: A review - Durlav Chowdhury; Rohan Sahu; Maikala Muskan Rao; Avijit Ghosh; Swarnalata Garai; Surendra H. Bodakhe (Next Research, 2026)

Gamma irradiation- induced zearalenone reduction in pearl millet and finger millet: cytotoxicity assessment and quality attributes - Muskan Kumari; Rupali Ambolikar; Sachin N. Hajare; Satyendra Gautam; Anil Kumar Chauhan (Food Research International, 2026)

Genome-wide identification and characterization of GATA transcription factors in Avena sativa L. and expression profiling under salinity stress - Muskan Bokolia; Tanu Singh; Nandni Goyal; Avneesh Kumar; Kashmir Singh; Baljinder Singh (Journal of Applied Genetics, 2026)

Trichothecium pseudoroseum sp. nov. (Myrotheciomycetaceae, Hypocreales) From Asia Revealed by Morphology and Multigene Phylogeny - Muhammad Binyamin Khan; Najam‐ul‐Sehar Afshan; Muhammada Jabeen; Muskan Amjad; Sardar Ali; Entaj Tarafder; Samantha C. Karunarathna; Ting Chi Wen (New Zealand Journal of Botany, 2026)
Trichothecium pseudoroseum sp. nov. is described from Yunnan Province, China, and Azad Jammu & Kashmir, Pakistan, based on morphological characteristics and multigene phylogenetic analyses. It is distinguished by its conidiophores, which arise directly from the substrate, are unbranched, solitary, long, slender, septate, slightly curved, smooth‐walled, and hyaline; the conidiogenous cells are smooth, hyaline, located at the apex, slightly swollen, and monoblastic, producing conidia that are ellipsoid, oblong, or pyriform in shape, asymmetrical, one‐septate, and smooth‐walled. To confirm its taxonomic placement, a multigene phylogenetic analysis based on Large Subunit and Internal Transcribed Spacer sequences was conducted, confirming it as an undescribed species and naming it as T. pseudoroseum . The fungus was isolated from the leaves of Trifolium sp., representing the first report of a Trichothecium species on this host. A full description, illustrations, and phylogenetic analysis results for T. pseudoroseum are provided, with comparisons to closely related taxa. This finding extends the known host range of T. pseudoroseum and provides new insights into its biodiversity and interactions with the Trifolium sp.

Deep learning for stenotic nares classification in brachycephalic dogs - Muskan Chauhan; Yatender Kumar (Veterinary Research Communications, 2026)

First report of leaf blight of garlic caused by Alternaria alternata in Himachal Pradesh, India - Thakur Muskan; Gupta Meenu; S. K. Sharma; Singh Anupama (Indian Phytopathology, 2026)

Computational discovery of DENV-3 RdRp allosteric inhibitors: biological evaluation and mechanistic studies - Gokul Krishnan Nagendran; Swati Fageria; Divya Bhatt; Neetu Malya; Akansha Belwal; Shruti Gautam; Muskan Singhal; Ayesha Fatima; Mamta Choudhary; Vineeta Rai; Chetan D. Meshram; Sathish Kumar Mudedla (Molecular Diversity, 2026)

Harnessing the therapeutic potential of nano-dimensions in managing psoriasis: From concept to properties - Ishu Garg; Neelam Singh; Shivani Rawat; Gagandeep Singh; Chaitanya Vinayak Narayan; Puneet Gupta; Mahalaxmi Muskan (Next Research, 2026)

A potent and selective P2 × 7R antagonist ameliorates neuropathic pain by suppressing inflammation and oxidative stress in a mouse chronic constriction injury model - Imran Malik; Aleena Muskan; Abid Mahmood; Babar Murtaza; Jamshed Iqbal (Inflammopharmacology, 2026)

Genome wide identification and characterization of Dof transcription factor and its expression analysis under salinity stress in Avena sativa L - Muskan Bokolia; Tanu Singh; Jangala chandini priya; Kashmir Singh; Baljinder Singh (Ecological Genetics and Genomics, 2026)

Urbanization and water bodies: a critical review to understand impacts and mitigation strategies in Indian cities - Aamod Kumar Karmaksh; Muskan Diwan; Ashwani Kumar (Environment Systems and Decisions, 2026)

Imidazole Scaffolds against Staphylococcus aureus and MRSA: a medicinal chemistry review - Supriyo Saha; Muskan Singh; Nikita Thapliyal; Shakir Ahamad; Shahnawaz Ali Bhat; Vikash Jakhmola (Molecular Diversity, 2026)

Unveiling the glucan profile: a comparative study of Lion’s Mane and Shiitake mushrooms - C. S. Keerthana; Rozy Kumari; Muskan Beura; Sumit Sharan; Susheel Kumar Sharma; Ananta Ganjoo; Anil Dahuja; Veda Krishnan (Natural Product Research, 2026)

The nano-revolution in food preservation: A review of advanced silver nanoparticle packaging - Kaustubh Singh; Shraddha Prakash; Deepak Choudhury; Digvir S. Jayas; Muskan Kumari; Rakesh K. Singh; Rupali Koundal; Anil Kumar Chauhan (Food Control, 2026)

Evaluating various vegetation indices in triangle method to enhance high-resolution soil moisture estimation - Bharatkumar S. Prajapati; Sonu Kumar; Rajendra Prasad; Prashant Kumar Srivastava; Jyoti Sharma; Shubham Kumar Singh; Manika Gupta; Muskan Dua (Advances in Space Research, 2026)

Protective Effect of Cordyceps militaris Extract Against Cigarette Smoke Extract Induced Neurodegeneration in Zebrafish Model - Paritosh Sharma; Dev Goyal; Muskan Thakur; Arun Parashar (Neurotoxicity Research, 2026)

Circular economy in action: palm oil kernel biochar and boiler ash enhance growth of Amaranthus viridis via ROS-induced antioxidants modulation - Jamilah Syafawati Yaacob; Muskan Sheba; Guan Cong Lee; Rosazlin Abdullah; Lili Syahani Rusli; Qazi Fariduddin; Laavanya Nyanasaigran; Nur Sa’adah Abdul Halim; Abdullah Abdul Rahman; Noor Sharina Mohd Rosli (Environmental Science and Pollution Research, 2026)

A review on novel strategies to combat multidrug resistance in pathogenic bacteria exploiting synergism between essential oil and antibiotics - Ishita Mazumder; Muskan Rehman; Falguni Deshmukh; Shrushti Shah; Akshita Singh; Sudha Ramaiah; Elizabeth Annie George; Anand Anbarasu (World Journal of Microbiology and Biotechnology, 2026)

Development of a Novel Pan-Species Multi-Epitope Vaccine (PS-MEV) Targeting Nine Staphylococcus Species to Combat Antibiotic Resistance - Allah Rakha Yaseen; Muhammad Suleman; Mahnoor Habib; Tehreem Arshad; Muskan Fatima; Ayesha Arif; Hafiza Sadia Rasool (Probiotics and Antimicrobial Proteins, 2026)

The Influence of Gut Microbiome on Alpha-Synuclein Aggregation: Implications for Parkinson’s Disease Pathogenesis - Muskan Sain; Shital Rani; Suraj Pratap Singh; Pritiman Pothal; Shubham Yadav; Ashish Suttee; Akhilesh Kumar; Santosh Kumar; Pavitra Ranawat; Gurpal Singh; Ravi Pratap Barnwal (Molecular Neurobiology, 2026)

Assessment of Hippocampal, Prefrontal Cortical, and Striatal Dopaminergic Circuitry Underlying Altered Social Behavior in Diabetes - Arun Parashar; Vineet Mehta; Udayabanu Malairaman; Muskan Thakur; Varsha Sharma (Molecular Neurobiology, 2026)

Impacts of microplastics, fluoride and mancozeb on tomato plant growth and rhizosphere microbial dynamics: A metagenomic analysis - Ajay KUMAR; Rajni SHARMA; Muskan BOKOLIA; Riyapi DAS; Sanjiv KUMAR; Ravindresh CHABBRA; Baljinder SINGH (Pedosphere, 2025)

Preparation of fungal biocomposite for environment friendly packaging of plant saplings - Mallika Saini; Muskan Kamboj; Ranjeeta Bhari; Dhandeep Singh (World Journal of Microbiology and Biotechnology, 2025)

Unraveling Non-coding RNAs and dysregulation of TGF-β signalling in cardiorenal syndrome, a focused review for molecular and clinical applications - Manpreet Kaur; Muskan Middha; Vinod Sharma; Neha Dahiya; Varsha Singh (Molecular Biology Reports, 2025)

Bioinformatics and immunoinformatics approaches in the design of a multi-epitope vaccine targeting CTLA-4 for melanoma treatment - Fatima Noor; Samiah Shahid; Muskan Fatima; Syed Zeeshan Haider; Zafer Saad Al Shehri; Faez Falah Alshehri; Abdur Rehman (Molecular Diversity, 2025)

Green ambitions: do environmental controversies and reduction targets alter environmental innovation impacts? - Saeed Rabea Baatwah; Muskan Sahu; Waleed M. Alahdal; Mohammed Bajaher (Environment, Development and Sustainability, 2025)

Toxicological evaluation of 4-methylimidazole: Research advances, health concerns and regulatory perspectives - Shikha; Keerti Gautam; Muskan Sharma (Toxicology Letters, 2025)

Allelopathic influence of Morus alba and Grewia optiva on growth and performance of pulse crops - Muskan Sharma; Navjot Singh Kaler; Somdutt Sharma; Ripul Sharma; Shiwangee Sharma; Arti Ghabru (Forest Ecology and Management, 2025)

Jasmonic Acid: A Key Elicitor of Cold Stress Tolerance in Horticultural Crops - Izhar Ullah; Muhammad Hamza; Noor ul Ain; Heba I. Mohamed; Murad Muhammad; Yaqoob Sultan; Muskan Alam Khan; Abdul Basit (Journal of Plant Growth Regulation, 2025)

Phospholipase C activator 3m3FBS reverses the synergistic toxicity of arsenic and cadmium - Manika Garg; Aiysha Siddiq Khan; Muskan Verma; Anupam Chawla; Pawan Yadav; Yogita Rawat; Asghar Ali; Somendu Kumar Roy; Mohan Kamthan (Journal of Trace Elements in Medicine and Biology, 2025)

Designing nickel nanoparticle-doped porous carbon using bio-based covalent organic framework for hydrogenation of levulinic acid: A sustainable approach towards upgradation of a bioplatform molecule - Shradhanjali Samal; Muskan Memon; Soyeb Pathan; Sonal Thakore (Journal of Environmental Chemical Engineering, 2025)

A comprehensive review of synthetic and semisynthetic xanthine oxidase inhibitors: identification of potential leads based on in-silico computed ADME characteristics - Rupali Rana; Anchal Sharma; Nitish Kumar; Aanchal Khanna; Jyoti; Muskan Dhir; Harmandeep Kaur Gulati; Jatinder Vir Singh; Preet Mohinder Singh Bedi (Molecular Diversity, 2025)

Dissipation pattern, risk assessment and decontamination of residues of emamectin benzoate, fipronil and acetamiprid on bell pepper - Arzoo Bakshi; Ajay Sharma; Sapna Katna; Tanuja Banshtu; Nisha Devi; Arvind Kumar; Shubhra Singh; Sakshi Sharma; Pankaj Istatu Sharma; Ankur Tomar; Muskan Baltoo (Environmental Geochemistry and Health, 2025)

Specific Glycoprotein E (gE) Gene Based Nested Polymerase Chain Reaction Assay for Detection of Marek’s Disease Virus in Chickens - Muskan Bhadok; Adarsh Mishra; M. Manu; Chandra Shekhar Mukhopadhyay; Gurpreet Kaur; Yashpal Singh Malik (Agricultural Research, 2025)

Systems biology approach reveals succinyl-CoA and hydroxycitrate as potential therapeutics for the treatment of vulvovaginal candidiasis - Abhishek Sengupta; Sudeepti Kulshrestha; Ritu Redhu; Ankur Chaurasia; Payal Gupta; Muskan Syed; Pooja Vijayaraghavan; Somesh Gupta; Priyanka Narad (Next Research, 2025)

A novel method for detecting conformation-dependent β-glucans—single, double, and triple-helical from Shiitake mushroom - Shuvarghya Chakraborty; Muskan Beura; Konjengbam Sarda Devi; Akoijam Ratankumar Singh; CS Keerthana; Susheel Kumar Sharma; Archana Singh; Anil Dahuja; Veda Krishnan (Natural Product Research, 2025)

Adulticidal efficacy of silica nanoparticles synthesized from Phyllanthus emblica and Punica granatum against Callosobruchus chinensis (Linnaeus, 1758) (Coleoptera:Chrysomelidae) - Kiran Meena; Neetu Kachhwaha; Vareesh Baghela; Sumita Kachhwaha; Shilpa Yadav; Muskan Kachhwaha (Journal of Stored Products Research, 2025)

Upcycling of electronic waste into a Cu-based metal–organic framework: From cell phone to a disposable electrochemical bilirubin sensor - Soyeb Pathan; Jeethu Raveendran; Muskan Memon; Varsha Chavda; K Niyas; Jagadeesh Bayry; P. Abdul Rasheed (Chemical Engineering Journal, 2025)

Molecular mechanisms and treatment strategies for estrogen deficiency-related and glucocorticoid-induced osteoporosis: a comprehensive review - Satyajit Mohanty; Anwesha Sahu; Tuhin Mukherjee; Sneha Kispotta; Payel Mal; Muskan Gupta; Jeet Kumar Ghosh; Pranav Kumar Prabhakar (Inflammopharmacology, 2025)

Dissipation kinetics, safety evaluation and decontamination of residues of the combi-formulation emamectin benzoate 1.50% + fipronil 3.50% SC in/on chilli - Muskan Baltoo; Tanuja Banshtu; Sapna Katna; Ajay Sharma; Sakshi Sharma; Arzoo Bakshi; Siddhant Thakur (Environmental Geochemistry and Health, 2025)

Pomegranate based agroforestry systems for sustainable agriculture, achieving food security and mitigating climate change through carbon sequestration in Northwest Himalayas - Shiwangee; Navjot Singh Kaler; Muskan Sharma; Somdutt Sharma; Ajit Sharma (Agroforestry Systems, 2025)

Peptide-Based Nanoparticles from Agricultural and Food Waste: Applications in Smart Food Packaging - Pooja yadav; Nishita Makkar; Muskan Jain; Ruby Prakash (International Journal of Peptide Research and Therapeutics, 2025)

Echoes of change: dynamics of air quality and health in the new normal - Muskan Agarwal; Isha Goyal; Gunjan Goswami; Simran Bamola; Anita Lakhani (Air Quality, Atmosphere & Health, 2025)

Environmental impact analysis of crop residue burning in Madhya Pradesh: A multivariate comparison across key crops - Nihal Singh Khangar; T. Mohanasundari; Muskan Bisla; K. Thomas Felix; A. R. Durga (Environmental Monitoring and Assessment, 2025)

Chemical composition, mutagenicity, and cytotoxicity of urban submicron particulate matter (PM1) in Agra, India - Gunjan Goswami; Simran Bamola; Muskan Agarwal; Isha Goyal; Amla Chopra; Alok Pandey; Anita Lakhani (Science of The Total Environment, 2024)

Efficacy of Nigella sativa seed oil against psychophysical stress induced irritable bowel syndrome and anxiety-like symptoms in Wistar rats - Madhu Sharma; Swati Rana; Shiwangi Aggarwal; Aitizaz Ul Ahsan; Muskan Budhwar; Sweety Mehra; Subhash Chandra Sahoo; Mani Chopra (Psychopharmacology, 2024)

Antidiabetic potential of thiazolidinedione derivatives with efficient design, molecular docking, structural activity relationship, and biological activity: an update review (2021–2023) - Anchal Sharma; Nitish Kumar; Harmandeep Kaur Gulati; Rupali Rana; Jyoti; Aanchal Khanna; Muskan; Jatinder Vir Singh; Preet Mohinder Singh Bedi (Molecular Diversity, 2024)

Cyto and Genoprotective Potential of Tannic Acid Against Cadmium and Nickel Co-exposure Induced Hepato-Renal Toxicity in BALB/c Mice - Madhu Sharma; Pooja Devi; Surbhi Kaushal; Aitizaz ul-Ahsan; Sweety Mehra; Muskan Budhwar; Mani Chopra (Biological Trace Element Research, 2024)

SMILEY—assistive application to support social and emotional skills in SPCD individuals - Muskan Chawla; Surya Narayan Panda; Vikas Khullar (Medical & Biological Engineering & Computing, 2024)

Unveiling the geoheritage, cultural geomorphology and geotourism potential of Zanskar region, NW Himalaya, India - Mohammad Irfan; Sareer Ahmad Mir; Bikram Singh Bali; Ahsan Afzal; Naseer Ahmad Bhat; Nayeem Bhat; Asif Bashir; Muskan Nazir (Geomorphology, 2024)

Fault system dynamics of the Kashmir, NW Himalaya, India using continuous GPS observations and geomorphic evidences - Muskan Nazir Dar; Bikram Singh Bali; Sareer Ahmad Mir; Ahsan Afzal Wani (Journal of Geodynamics, 2024)

Use of antioxidants to retard aging of bitumen: A review - Muskan Verma; Nikhil Saboo (Environmental Science and Pollution Research, 2024)

Gestational Fisetin Exerts Neuroprotection by Regulating Mitochondria-Directed Canonical Wnt Signaling, BBB Integrity, and Apoptosis in Prenatal VPA-Induced Rodent Model of Autism - Sweety Mehra; Aitizaz Ul Ahsan; Madhu Sharma; Muskan Budhwar; Mani Chopra (Molecular Neurobiology, 2024)

Thermo-chemical behaviour of Dunaliella salina biomass and valorising their biochar for naphthalene removal from aqueous rural environment - Muskan Nama; Gopi Satasiya; Tarini Prasad Sahoo; Pareshkumar G. Moradeeya; Shreya Sadukha; Kirti Singhal; Hitesh T. Saravaia; Ramalingam Dineshkumar; Madhava Anil Kumar (Chemosphere, 2024)

Bioprocessing 4.0 in biomanufacturing: paving the way for sustainable bioeconomy - Kamini Pandey; Muskan Pandey; Vinay Kumar; Upasana Aggarwal; Barkha Singhal (Systems Microbiology and Biomanufacturing, 2024)

Valorization of sugarcane bagasse with in situ grown MoS2 for continuous pollutant remediation and microbial decontamination - Rahul Ranjan; Smruti B. Bhatt; Rohit Rai; Sanju Kumari Sharma; Muskan Verma; Prodyut Dhar (Environmental Science and Pollution Research, 2024)

Structural and functional characterisation of Maillard reaction products from casein-acid hydrolysate-sugars model system using multi-spectroscopic approach - Harsha V. Sail; Ashwini D. Jagdale; Muskan R. Thakur; Rashmi S. Tupe (International Dairy Journal, 2024)

Characterising temporal variability of PM2.5/PM10 ratio and its correlation with meteorological variables at a sub-urban site in the Taj City - Simran Bamola; Gunjan Goswami; Surat Dewan; Isha Goyal; Muskan Agarwal; Arsh Dhir; Anita Lakhani (Urban Climate, 2024)

Exploration of bioactive molecules from Tinospora cordifolia and Actinidia deliciosa as an immunity modulator via molecular docking and molecular dynamics simulation study - Varun Kishor Bagal; Sanket Somnath Rathod; Muskan Musa Mulla; Swaranjali Chandrakant Pawar; Prafulla Balkrishna Choudhari; Vijaykumar Tanajirao Pawar; Deepak Vamanrao Mahuli (Natural Product Research, 2023)

Lentinan, β-glucan from Shiitake (Lentinula edodes): A review on structure, conformational transition, and gastro-intestinal interaction contributing towards its anti-diabetic potential - Shuvarghya Chakraborty; Muskan Beura; Susheel Kumar Sharma; Archana Singh; Anil Dahuja; Veda Krishnan (Trends in Food Science & Technology, 2023)

Boosting the efficiency of supported undecamolybdophosphate catalyst by tailoring acid-redox properties for direct oxidative cross-esterification of aldehydes - Yas Murani; Muskan Memon; Shreya Singh; Soyeb Pathan (Chemical Engineering Journal, 2023)

Mucoadhesive, Fluconazole-Loaded Nanogels Complexed with Sulfhydryl-β-cyclodextrin for Oral Thrush Treatment - Farwa Muskan Khalid; Muhammad Ijaz; Arshad Mahmood; Muhammad Khurram Waqas; Talib Hussain; Mulazim Hussain Asim; Nadeem Ahmad; Shumaila Arshad; Masood Ur Rehman; Imran Nazir (AAPS PharmSciTech, 2023)

The role of chemical fractionation in risk assessment of toxic metals: a review - Isha Goyal; Muskan Agarwal; Simran Bamola; Gunjan Goswami; Anita Lakhani (Environmental Monitoring and Assessment, 2023)

Neuroprotective Efficacy of Fisetin Against VPA-Induced Autistic Neurobehavioral Alterations by Targeting Dysregulated Redox Homeostasis - Sweety Mehra; Aitizaz Ul Ahsan; Madhu Sharma; Muskan Budhwar; Mani Chopra (Journal of Molecular Neuroscience, 2023)

Two-way strategy for enhanced pectinase production: Random mutagenesis and utilization of a halophytic biomass - Asma Hanif; Uroosa Ejaz; Khwaja Ali Hasan; Malaika Karim; Fehmida Suleman; Muskan Siddiq; Syed Faraz Moin; Zainul Abideen; Muhammad Sohail (Biocatalysis and Agricultural Biotechnology, 2023)

Rising winter temperatures might augment increasing wheat yield in Gangetic Plains - Mayank Shekhar; Muskan Singh; Shaktiman Singh; Anshuman Bhardwaj; Rupesh Dhyani; Parminder S. Ranhotra; Lydia Sam; Amalava Bhattacharyya (Theoretical and Applied Climatology, 2022)

Bintaro (Cerbera odollam and Cerbera manghas): an overview of its eco-friendly use, pharmacology, and toxicology - Mansi Saxena; Ekta B. Jadhav; Mahipal Singh Sankhla; Muskan Singhal; Kapil Parihar; Kumud Kant Awasthi; Garima Awasthi (Environmental Science and Pollution Research, 2022)

Emergence of nutriments as a nascent complementary therapy against antimicrobial resistance - Rajwinder Kaur; Muskan Kanotra; Ankita Sood; Ahmed A. H. Abdellatif; Saurabh Bhatia; Ahmed Al-Harrasi; Lotfi Aleya; Celia Vargas-De-La-Cruz; Tapan Behl (Environmental Science and Pollution Research, 2022)

Precision Postbiotics and Mental Health: the Management of Post-COVID-19 Complications - Muskan Pandey; Archana Bhati; Kumari Priya; K. K. Sharma; Barkha Singhal (Probiotics and Antimicrobial Proteins, 2022)

Antimicrobial activity of bacteria associated with the rhizosphere and phyllosphere of Avena fatua and Brachiaria reptans - Muskan Ali; Sadia Walait; Muhammad Farhan Ul Haque; Salma Mukhtar (Environmental Science and Pollution Research, 2021)

Pertinence of nutriments for a stalwart body - Rajwinder Kaur; Ankita Sood; Muskan Kanotra; Sandeep Arora; Vetriselvan Subramaniyan; Saurabh Bhatia; Ahmed Al-Harrasi; Lotfi Aleya; Tapan Behl (Environmental Science and Pollution Research, 2021)

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

C-terminally encoded peptides (CEPs) are potential mediators of abiotic stress response in plants - Sakshi Aggarwal; Ashish Kumar; Muskan Jain; Jebi Sudan; Kapil Singh; Sumita Kumari; Ananda Mustafiz (Physiology and Molecular Biology of Plants, 2020)

Computational insights of K1444N substitution in GAP-related domain of NF1 gene associated with neurofibromatosis type 1 disease: a molecular modeling and dynamics approach - Ashish Kumar Agrahari; Meghana Muskan; C. George Priya Doss; R. Siva; Hatem Zayed (Metabolic Brain Disease, 2018)

Withania somnifera as a Potential Anxiolytic and Anti-inflammatory Candidate Against Systemic Lipopolysaccharide-Induced Neuroinflammation - Muskan Gupta; Gurcharan Kaur (NeuroMolecular Medicine, 2018)

Withania somnifera as a potential anxiolytic and immunomodulatory agent in acute sleep deprived female Wistar rats - Taranjeet Kaur; Harpal Singh; Rachana Mishra; Shaffi Manchanda; Muskan Gupta; Vedangana Saini; Anuradha Sharma; Gurcharan Kaur (Molecular and Cellular Biochemistry, 2017)

The paradox of marine heterotrophic nitrogen fixation: abundances of heterotrophic diazotrophs do not account for nitrogen fixation rates in the E astern T ropical S outh P acific - Kendra A. Turk‐Kubo; Muskan Karamchandani; Douglas G. Capone; Jonathan P. Zehr (Environmental Microbiology, 2014)
Summary Results of recent modelling efforts imply denitrification‐influenced waters, such as those in the E astern T ropical S outh P acific ( ETSP ), may support high rates of biological nitrogen fixation ( BNF ), yet little is known about the N 2 ‐fixing microbial community in this region. Our characterization of the ETSP diazotrophic community along a gradient from upwelling‐influenced to oligotrophic waters did not detect cyanobacterial diazotrophs commonly found in other open ocean regions. Most of the nifH genes amplified by polymerase chain reaction ( PCR ) from DNA and RNA samples clustered with γ‐proteobacterial nifH sequences, although a novel T richodesmium phylotype was also recovered. Three quantitative PCR assays were developed to target γ‐proteobacterial phylotypes, but all were found to be present at low abundances. An analysis of the expected BNF rates based on abundances and plausible cell‐specific N 2 fixation rates indicates that these γ‐proteobacteria are unlikely to be responsible for previously reported BNF rates from corresponding samples. Therefore, the organisms responsible for the measured BNF rates remain poorly understood. Furthermore, there is little direct evidence, at this time, to support the hypothesis that heterotrophic N 2 fixation contributes significantly to oceanic BNF rates based on our analysis of heterotrophic cell‐specific N 2 fixation rates required to explain BNF rates reported in previously published studies.